2014
DOI: 10.7314/apjcp.2014.15.21.9265
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Clinical Significance of miRNA-34a in Colorectal Cancer

Abstract: Background: The aim of this study was to investigate differences of miRNA-34a expression in benign and malignant colorectal lesions. Materials and Methods: Samples of cancer, paraneoplastic tissues and polyps were selected and total RNA was extracted by conventional methods for real-time PCR to detect the miRNA34a expression. In addition, the LOVO colorectal cancer cell line was cultured, treated with the demethylating agent 5-azacytidine and screened for differentially expressed miRNA-34a. Results: After the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
(28 reference statements)
1
7
0
1
Order By: Relevance
“…This accordance with the study of Ma et al who found that Polyps tissues had significantly higher miRNA34a gene expression than para-neoplastic and colorectal cancer tissue samples [17] .…”
Section: Discussionsupporting
confidence: 92%
“…This accordance with the study of Ma et al who found that Polyps tissues had significantly higher miRNA34a gene expression than para-neoplastic and colorectal cancer tissue samples [17] .…”
Section: Discussionsupporting
confidence: 92%
“…miR-34a-5p expression has been shown to be directly regulates the expression of proteins involved in cell cycle, differentiation, apoptosis, and antagonizes processes, including cervical, ovarian and testicular cancer (19,20). Ma et al conducted a series of studies on miR-34a-5p, and were the first to confirm its pro-apoptotic function (21). Moreover, miR-34a-5p has been found to inhibit cell proliferation and invasion in vitro, which suggested that miR-34a-5p might play a role in inhibiting tumor recurrence (22).…”
Section: Discussionmentioning
confidence: 99%
“…Through binding target mRNA molecules, miRNAs generally downregulate gene expression and can influence cell proliferation, apoptosis, and the cell cycle 7–9. Dysregulated miRNA expression is a common feature in human cancers,10,11 and previous studies have demonstrated that several miRNAs are dysregulated in colorectal cancer (CRC), and associated with its progression 12–14. Aberrant expression of miRNAs is increasingly recognized as involved in the inappropriate stimulation of cellular programs, such as autophagy 15,16…”
Section: Introductionmentioning
confidence: 99%